EFEKTIVITAS FLIPBOOK BERBASIS KURIKULUM MERDEKA DENGAN MODEL COURSE REVIEW HORAY UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI DAN LITERASI SISWA MI MIFTAHUL AKHLAQIYAH - Isfaidah Nur Anjani; Haryadi; Bernadus Wahyudi Joko Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of using Flipbook based on the Merdeka Curriculum and the Course Review Horay model in improving poetry writing skills and literacy of students at MI Miftahul Akhlaqiyah. This research uses an experimental design with two sample groups, class 5A as the experimental group with 35 students and class 5B as the control group with 33 students. The experimental group received treatment using Flipbook based on the Merdeka Curriculum and the Course Review Horay model, while the control group received conventional learning. Data were collected through poetry writing tests, literacy questionnaires, and student engagement observations. The results show that the experimental group experienced significant improvement in poetry writing and literacy, with a t-Value of 12.68 and a p-value of 0.000, while the control group showed no significant improvement. This proves that the application of technology in learning, such as using Flipbook and the active learning model Course Review Horay, can effectively improve students' poetry writing and literacy skills. This study suggests that elementary schools, especially MI, integrate technology and active learning models to improve the quality of students' literacy education.